Financial resource availability and corporate social responsibility expenditures in a sub‐Saharan economy: The institutional difference hypothesis - Julian, Scott D.; Ofori‐dankwa, Joseph C. (Strategic Management Journal, 2013)
Studies done in developed economies have demonstrated a positive relationship between financial resource availability and CSR . Arguments that we term the Institutional Difference Hypothesis ( IDH ) drawn from the institutional literature, however, suggest that institutional differences between developed and developing economies are likely to result in different CSR implications. Integrating the logic of IDH with insights from slack resources theory, we argue that there exists a negative relationship between financial resource availability and CSR expenditures for firms in G hana, a sub‐ S aharan A frican emerging economy. We use lagged data from the G hana I nvestment P romotion C entre and find that Return on Sales, Return on Equity, and Net Profitability were consistently associated with lower CSR expenditures. We highlight the implications of our findings for research and managers . Copyright © 2013 John Wiley & Sons, Ltd.